2021
DOI: 10.1155/2021/8141563
|View full text |Cite
|
Sign up to set email alerts
|

Liposome Extract of Stachys pilifera Benth Effectively Improved Liver Damage due to Bile Duct Ligation Rats

Abstract: Herbal medicines harbor essential therapeutic agents for the treatment of cholestasis. In this study, we have assessed the anticholestatic potential of Stachys pilifera Benth’s (SPB’s) hydroalcoholic extract encapsulated into liposomes using bile duct ligation- (BDL-) induced hepatic cholestasis in rats. Aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), malondialdehyde (MDA), total thiol (T-SH) content, protein carbonyl (PCO), total bilirubin (TBIL), albumin (ALB), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…Serum biochemical analysis indicated that the levels of AST, ALT and TBA were not changed significantly. These biochemical changes are similar to previous findings in humans [ 24 ], but these results are different from Shakerinasab et al and Moslemi et al’s reports [ 25 , 26 ] that SD rats after BDL for 7 days, AST, ALT and TBA were increased, also Nasehi Z, et al [ 27 ] found the levels of serum AST, ALT and TBA were increased in SD rats after BDL for three weeks. Ghallab A, et al[ 28 ] found that ALT, AST and TBA increased in the acute phase, reaching a peak on days 1 and 2 after BDL, but decreased significantly below control levels in the chronic phase, with normalization on day 21.…”
Section: Discussionsupporting
confidence: 75%
“…Serum biochemical analysis indicated that the levels of AST, ALT and TBA were not changed significantly. These biochemical changes are similar to previous findings in humans [ 24 ], but these results are different from Shakerinasab et al and Moslemi et al’s reports [ 25 , 26 ] that SD rats after BDL for 7 days, AST, ALT and TBA were increased, also Nasehi Z, et al [ 27 ] found the levels of serum AST, ALT and TBA were increased in SD rats after BDL for three weeks. Ghallab A, et al[ 28 ] found that ALT, AST and TBA increased in the acute phase, reaching a peak on days 1 and 2 after BDL, but decreased significantly below control levels in the chronic phase, with normalization on day 21.…”
Section: Discussionsupporting
confidence: 75%
“…NO molecules are highly reactive mediators released mostly by endothelial and Kuppfer cells of the liver to respond to various liver injuries [ 53 ]. Previous studies have shown that NOx significantly increases in gentamicin treated rats [ 2 ] and various nutraceutical molecules have proven to have beneficial effects [ 54 , 55 , 56 ]. Palm fruit extract also was proven to have protective effects against liver cytoarchitecture damage by gentamicin administration [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cur has effects such as anti-inflammatory, antioxidant, and anticoagulant activities. Cur is a hydrophobic drug that is usually used in nanocarriers such as nanoliposomes to increase its solubility, absorption, and efficacy [9,17,25,40]. In recent years, several efforts have been made to develop GO-based nanocarriers, which have been widely used in gene and drug delivery.…”
Section: Discussionmentioning
confidence: 99%